Induction of Malaria parasite migration by synthetically tunable microenvironments - Perschmann, Nadine; Hellmann, Janina K.; Frischknecht, Friedrich; Spatz, Joachim P. (Nano letters, 2011)
Interaction of Plasmodium sporozoites, the forms of the malaria parasite transmitted by the mosquito, with its microenvironment in form of adhesion and migration is essential for the successful establishment of infection. Myosin-based sporozoite migration relies on short and dynamic actin filaments. These are linked to transmembrane receptors, which in turn bind to the matrix microenvironment. In this work, we are able to define the characteristics that determine whether a matrix is favorable or adverse to sporozoite adhesion and motility using a specifically tunable hydrogel system decorated with gold nanostructures of defined interparticle spacing each equipped with molecules acting as receptor adhesion sites. We show that sporozoites migrate most efficiently on substrates with adhesion sites spaced between 55 and 100 nm apart. Sporozoites migrating on such substrates are more resilient toward disruption of the actin cytoskeleton than parasites moving on substrates with smaller and larger interparticle spacings. Plasmodium sporozoites adhesion and migration was also more efficient on stiff, bonelike interfaces than on soft, skinlike ones. Furthermore, in the absence of serum albumin, previously thought to be essential for motility, sporozoite movement was comparable on substrates functionalized with RGD- and RGE-peptides. This suggests that adhesion formation is sufficient for activating migration, and that modulation of adhesion formation and turnover during migration is efficiently controlled by the material parameters of the microenvironment, that is, adhesion site spacing and substrate stiffness. Our results and approaches provide the basis for a precise dissection of the mechanisms underlying Plasmodium sporozoites migration.
Gesehen am 23.07.2018